2006
DOI: 10.1037/0022-006x.74.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Self-system therapy as an intervention for self-regulatory dysfunction in depression: A randomized comparison with cognitive therapy.

Abstract: Self-system therapy (SST) is a new therapy based on regulatory focus theory (E. T. Higgins, 1997) for depressed individuals unable to pursue promotion goals effectively. The authors conducted a randomized trial comparing SST with cognitive therapy (CT) in a sample of 45 patients with a range of depressive symptoms to test 2 hypotheses: that SST would be more efficacious for depressed individuals characterized by inadequate socialization toward pursuing promotion goals and that SST would lead to greater reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 55 publications
(86 reference statements)
6
81
0
Order By: Relevance
“…However, the current study suggests that targeting perfectionism alone may not adequately address problems with self-regulation that are associated with, or amplify the negative effects of, perfectionism. Treatments like self-system therapy, which targets deficits in incentive motivation and teachings skills to enhance goal pursuit (Strauman et al, 2006), may be an especially promising approach for dealing with perfectionism.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current study suggests that targeting perfectionism alone may not adequately address problems with self-regulation that are associated with, or amplify the negative effects of, perfectionism. Treatments like self-system therapy, which targets deficits in incentive motivation and teachings skills to enhance goal pursuit (Strauman et al, 2006), may be an especially promising approach for dealing with perfectionism.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many goals of the treatment is to help clients reengage in promotion-focused behaviors. In a randomized trial comparing SST to cognitive therapy (Strauman et al, 2006 ), it was found to be more effective for individuals with a history of lack of socialization in promotion (i.e., deficits in the promotion system). This vulnerability of individuals to depression following severe promotion-related failures is another example of how the impact of failure within the two systems has very different consequences.…”
Section: Coping With Failurementioning
confidence: 99%
“…It is characterized by a pervasive low mood, loss of interest in usual activities, diminished ability to experience pleasure (anhedonia), withdrawal of interest, feelings of worthlessness, and suicidal tendencies (Percaccio et al 2005;SaletuZyhlarz et al 2003;Schechter et al 2005;Strauman et al 2006). The pharmacological treatments for depression currently available include tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs), serotoninnoradrenergic reuptake inhibitors (SNRIs), and other atypical antidepressant drugs such as monoamine oxidase inhibitors (MAOIs; Nemeroff 2007).…”
Section: Introductionmentioning
confidence: 98%